2005
DOI: 10.1051/lait:2004025
|View full text |Cite
|
Sign up to set email alerts
|

Colonic infusion with Propionibacterium acidipropionici reduces severity of chemically-induced colitis in rats

Abstract: -Propionibacteria are cheese starters, also studied for their probiotic potential. An interesting feature is the ability of some strains to synthesize nitric oxide (NO) from nitrate reduction. NO production is hypothesized to be the mechanism by which some probiotics improve the mucosal barrier in rats. We therefore investigated the ability of two Propionibacterium acidipropionici strains (TL15 & TL223), which differ in their in vitro production of NO, to improve colitis in rats. Three groups of rats in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…However, no clear relationship has been observed between soluble fiber and the presence of some fibrolytic bacteria that might act as a probiotic (Bacteroides spp., Butirivibrio fibrosolvens, Propionibacterium spp., and Ruminococus spp. ; Michel et al, 2005;Ohkawara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear relationship has been observed between soluble fiber and the presence of some fibrolytic bacteria that might act as a probiotic (Bacteroides spp., Butirivibrio fibrosolvens, Propionibacterium spp., and Ruminococus spp. ; Michel et al, 2005;Ohkawara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been proposed that some surface compounds should be involved in immunomodulatory effects of propionibacteria since removal of surface layer proteins decreased the in vitro induction of anti-inflammatory cytokines [171]. By their side, Michel et al [193] demonstrated that colonic infusion with P. acidipropionici reduced the severity of TNBS induced colitis in rats whereas Kajander et al [194] reported that the multispecies probiotic mixture containing…”
Section: Alleviation Of Ibdmentioning
confidence: 99%
“…Dairy propionibacteria display various probiotic properties either similar to or distinct from those reported for probiotic bifidobacteria and lactic acid bacteria (3). Although an anti-inflammatory potential of a few dairy propionibacterium strains was occasionally suggested in vitro (15) or in animals (22,24,31), no reliable observation was established in terms of strain variability and of specific mechanisms involved. In addition, supplementation with dairy propionibacteria in human randomized, placebo-controlled, double-blind trials has mainly concerned mixtures comprising probiotic bacteria assigned to genera other than Propionibacterium but rarely with propionibacteria alone (16).…”
mentioning
confidence: 99%